Infinitely many solutions for class of Navier boundary (p,q)-biharmonic systems - Mohammed Massar; El Miloud Hssini; Najib Tsouli (Electronic Journal of Differential Equations, 2012)
This article shows the existence and multiplicity of weak solutions for the (p,q)-biharmonic type system $$displaylines{ Delta(|Delta u|^{p-2}Delta u)=lambda F_u(x,u,v)quadhboxin Omega,cr Delta(|Delta v|^{q-2}Delta v)=lambda F_v(x,u,v)quadhboxin Omega,cr u=v=Delta u=Delta v=0quad hboxon partialOmega. }$$ Under certain conditions on F, we show the existence of infinitely many weak solutions. Our technical approach is based on Bonanno and Molica Bisci's general critical point theorem.